Provisioning Quality of Service of Wireless Telemedicine for E-Health Services: A Review - -, Mustafa Almahdi Algaet; Muhamad Noh , Zul Azri; Shibghatullah, Abdul Samad; -, Aouache Mustapha; -, Ali Ahmad Milad (2014)
In general, on-line medical consultation reduces time required for medical consultation and induces improvement in the quality and efficiency of healthcare services. The scope of study includes several key features of present day e-health applications such as X-ray, ECG, video, diagnosis images and other common applications. Moreover, the provision of Quality of Service (QoS) in terms of specific medical care services in e-health, the priority set for e-health services and the support of QoS in wireless networks and techniques or methods aimed at IEEE 802.11 to secure the provision of QoS has been assessed as well. In e-health, medical services in remote places which include rustic healthcare centres, ships, ambulances and home healthcare services can be supported through the applications of e-health services such as medical databases, electronic health data and the transferring of text, video, sound and images. Given this, a proposal has been made for a multiple service wireless networking with multiple sets of priorities. In relation to the terms of an acceptable QoS level by the customers of e-health services, prioritization is an important criterion in a multi-traffic network. The requirement for QoS in medical networking of wireless broadband has paved the way for bandwidth prerequisites and the live transmission or real-time medical applications. The proposed wireless network is capable of handling medical applications for both normal and life-threatening conditions as characterized by the level of emergencies. In addition, the allocation of bandwidth and the system that controls admittance designed based on IEEE 802.16 especially for e-health services or wireless telemedicine will be discussed in this study. It has been concluded that under busy traffic conditions, the proposed architecture can used as a feasible and reliable infrastructure network for telemedicine.